Readiness for practice in undergraduate nursing students during the COVID-19 pandemic: a crossectional study - Basso, I.; Gonella, S.; Londa, M.; Airoldi, C.; Chilin, G.; Follenzi, A.; Dal Molin, A.; Dimonte, V. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The Coronavirus disease 2019 (COVID-19) pandemic negatively impacted nursing students’ opportunity to gain experience through clinical placement, potentially threatening their readiness for practice and their clinical competence. The aim of this study was to explore whether and to what extent the thirdyear undergraduate nursing students perceived that their readiness for practice was impacted by changes to clinical placement and classroom learning implemented in response to the COVID-19 pandemic.Study design. Cross-sectional study.Methods. The study was conducted in a university of North-western Italy that provides nursing education across five sites. All sites stopped in-person classroom learning at the beginning of March 2020, but each site was free to decide whether to continue in-person clinical placement based on the local epidemiological situation. All 228 third-year nursing students who completed their degree by June 2020 were invited to participate. Data were collected via online questionnaire, which included the question “What impact do you think that COVID-19 safety measures employed by your nursing programme had on your readiness for practice?” Answers were given on a 5-point Likert scale (none, minimal, moderate, major, and severe). Explanatory variables were collected at the individual, nursing programme, and university site levels.Results. A total of 126 (response rate 55.3%) nursing students completed the questionnaire. Overall, 84 (66.7%) perceived that COVID-19 safety measures had a moderate to severe impact on their readiness for practice. These students often had lower grade point averages (p=0.037) and received no clinical placement during the pandemic (72.6% vs 90.5% of students who reported no or minimal impact, p=0.022). Average duration of third-year clinical placement was also lower among these students, though it was not statistically significant. No differences emerged at the university site level.Conclusions. Despite important advances in technology-based educational activities, clinical placement remains the best educational strategy to allow nursing students to feel prepared to work effectively during a pandemic.